Revisiting Tregs in cancer and beyond: immunological control and therapeutic potential - Zheng, Lei; Wu, Dan; Xie, Hongwei; Zhao, Hai (Frontiers in Immunology, 2025)
Tregs play a crucial role in maintaining immune homeostasis, but their involvement in cancer and other diseases has made them a focus of intense research. Tregs contribute to immune evasion by tumors and can affect responses to therapies. Understanding their mechanisms and the potential to manipulate them therapeutically is critical for improving cancer treatment strategies. This review aims to provide an updated perspective on the role of Tregs in cancer and beyond, with a focus on their immunological control mechanisms and therapeutic potential. We examine the recent advances in understanding Treg biology, their interaction with the tumor microenvironment, and the strategies developed to target Tregs for cancer immunotherapy. The review highlights the dual role of Tregs in promoting immune tolerance and in facilitating tumor progression. It discusses the various markers, transcription factors, and signaling pathways involved in Treg differentiation and function. Moreover, we explore the potential of targeting Tregs using novel therapeutic approaches, including monoclonal antibodies, checkpoint inhibitors, and gene editing. The review emphasizes emerging strategies for modulating Treg function in a way that enhances anti-tumor immunity while minimizing systemic autoimmunity.